Social Critique in the Lyrics of Parung Panjang Pride by Istantos: A Critical Discourse Analysis Based on Van Dijk’s Model: Kritik Sosial dalam Lirik Lagu Parung Panjang Pride Karya Istantos (Analisis Wacana Kritis Van Dijk) - Miftasari, Gigih; Budianto, Heri; Fasta, Feni (Universitas Muhammadiyah Sidoarjo, 2025)
This study examines the song Parung Panjang Pride by Istantos through the lens of critical discourse analysis, aiming to uncover how discourse in music can serve as a form of social critique. The song reflects the concerns of a member of the Parung Panjang community, voicing resistance against both local and national policymakers. It functions as a cultural response to marginalization caused by extractive industries and state negligence. Using Van Dijk’s model of critical discourse analysis, this research is grounded in a critical paradigm as well as concepts of music as discourse. The analysis focuses on three dimensions: text structure, social cognition, and social context. At the textual level, the lyrics juxtapose local pride with suffering caused by destructive mining operations. Istantos employs grounded, accessible language to portray environmental damage, social tensions, and community despair, while also affirming collective resistance through symbolic expression. In the social cognition dimension, the songwriter identifies as part of an oppressed yet resilient community, with an ideological belief in hip-hop as a vehicle for protest. At the level of social context, the song critiques power imbalances between residents, the government, and corporations. It highlights delayed infrastructure projects, weak law enforcement, and the socio-political neglect of Parung Panjang.